Effect of layering sequence on mechanical properties of woven kenaf/jute fabric hybrid laminated microwave-processed composites. Issue 2 (June 2022) - Singh, Manoj Kumar; Zafar, Sunny
In this research work, multi-layered composites of pure and hybrid woven fibre mats were fabricated using microwave-assisted compression moulding process. The hybrid composite consisted of jute and kenaf fibre as reinforcement having weight fraction of 29 ± 1%, while high-density polyethylene acted as the matrix. The laminate of multi-layered composites was fabricated by stacking the kenaf and jute woven fibre mats with high-density polyethylene matrix, resulting in different hybrid composites, i.e. JJJ, KKK, JKJ and KJK. JKJ exhibited maximum flexural strength of 55.64 ± 2.8 MPa, whereas KJK exhibited maximum flexural modulus of 3.65 ± 0.2 GPa. The tensile strength, impact strength and Shore D hardness were maximum in case of KKK composite, having the value of 60 ± 3 MPa, 31.8 ± 1.6 kJ/m 2 and 58 ± 2.9, respectively. It can be concluded that the stacking sequence has a nominal effect on flexural strength, tensile strength and impact strength of the composites.